Aging Neurovascular Unit and Potential Role of DNA Damage and Repair in Combating Vascular and Neurodegenerative Disorders - Li, Yan; Xie, Lv; Huang, Tingting; Zhang, Yueman; Zhou, Jie; Qi, Bo; Wang, Xin; Chen, Zengai; Li, Peiying (Frontiers in Neuroscience, 2019)
Progressive neurological deterioration poses enormous burden on the aging population with ischemic stroke and neurodegenerative disease patients, such as Alzheimers’ disease and Parkinson’s disease. The past two decades have witnessed remarkable advances in the research of neurovascular unit dysfunction, which is emerging as an important pathological feature that underlies these neurological disorders. Dysfunction of the unit allows penetration of blood-derived toxic proteins or leukocytes into the brain and contributes to white matter injury, disturbed neurovascular coupling and neuroinflammation, which all eventually lead to cognitive dysfunction. Recent evidences suggest that aging-related oxidative stress, accumulated DNA damage and impaired DNA repair capacities compromises the genome integrity not only in neurons, but also in other cell types of the neurovascular unit, such as endothelial cells, astrocytes and pericytes. Combating DNA damage or enhancing DNA repair capacities in the neurovascular unit represents a promising therapeutic strategy for vascular and neurodegenerative disorders. In this review, we focus on aging related mechanisms that underlie DNA damage and repair in the neurovascular unit and introduce several novel strategies that target the genome integrity in the neurovascular unit to combat the vascular and neurodegenerative disorders in the aging brain.